Cooperative frequency upconversion in Yb3+-Tb3+ codoped fluoroindate glass - Martins, E.; Araújo, Cid B. de; Delben, J. R.; Gomes, A. S. L.; Costa, B. J. da; Messaddeq, Younes [UNESP] (Elsevier, 1998)
We report the observation of cooperative frequency upconversion in a fluoroindate glass. The experiments were performed by exciting Yb3+-Tb3+ codoped samples with an infrared diode laser. The process is monitored through the green fluorescence emitted by Tb3+ ions due to a cooperative energy transfer from a pair of excited Yb3+ ions. © 1998 Elsevier Science B.V. All rights reserved.
Keywords: Energy transfer; Fluorescence; Semiconductor doping; Semiconductor lasers; Ytterbium compounds; Fluoroindate glass; Infrared diode lasers; Optical glass